Advances and challenges in the development of visual prostheses. - Eduardo Fernandez; Jose Antonio Robles (PLoS Biology)
The past 20 years have witnessed significant advancements in the field of visual prostheses, with developments spanning from early retinal implants to recent cortical approaches. This Perspective looks at some of the remaining challenges to achieve the ambitious clinical goals that these technologies could enable.